The sympathetic circularity function in English: an intonation corpus-driven analysis - Romero Trillo, Jesús (Estudios Ingleses de la Universidad Complutense, 2012)
The study of language functions at a large scale poses a series of difficulties that have to be overcome by a combination of detailed analyses and generalizations. In this sense, discourse markers have fascinated many scholars because they combine a localized interpretation of a piece of discourse with a notable capacity of being used in many different contexts, and with a wide variety of functions. This article describes the ‘sympathetic circularity function’ in a section of the London-Lund Corpus, and its prosodic and contextual realization by discourse markers. The study discusses the relevance of this function from a theoretical perspective and shows that the use of the discourse markers that realize it is not random but, rather, follows a cognitive pattern of proto-typicality that models the cognitive status of the speakers in the corpus. The analysis will show that the identification of the functions of language, and of their realization by discourse markers, is an essential tool to describe language and the cognitive basis of language functions in the speech of a community of discourse users.